2007
DOI: 10.1248/bpb.30.2058
|View full text |Cite
|
Sign up to set email alerts
|

Involvment of Endogenous Prostaglandin in Emodin-Evoked Rat Colonic Anion Secretion

Abstract: The mammalian colon is the final station of the gastrointestinal (GI) tract, where the organism has the last opportunity to modify the electrolyte contents in the feces with balanced absorptive and secretory activities. Colonic epithelium, a typical electrolyte-transporting epithelium, lines the surface of both crypts and villi, and plays an important role in the maintenance of water and electrolyte balance.Anthraquinones are present in the roots, bark or leaves of numerous plants such as senna, cascara, aloe,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Emodin applied to the basolateral side of the colonic mucosa/submucosa preparations evoked an increase in I SC (Figure 1A), which was similar to that observed in the colonic mucosa‐only preparations (Xu et al ., 2007). Mucosal addition of emodin produced only a small increase in I SC (Figure 1A).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Emodin applied to the basolateral side of the colonic mucosa/submucosa preparations evoked an increase in I SC (Figure 1A), which was similar to that observed in the colonic mucosa‐only preparations (Xu et al ., 2007). Mucosal addition of emodin produced only a small increase in I SC (Figure 1A).…”
Section: Resultssupporting
confidence: 81%
“…The polygonum multiflorum rhubarb roots were purchased from Beijing‐tongrentang, Beijing, China. As described previously (Xu et al ., 2007), the air‐dried roots were powdered and extracted with 80% ethanol. The combined solution was concentrated to afford a residue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the concentration of BSO used in the present investigation is clinically achievable. In addition, it is notable that phase I studies of BSO administered with the anticancer drug melphalan demonstrated that continuous infusion of BSO was relatively non-toxic and resulted in depletion of tumor GSH (16,17). This study adds to a growing body of evidence that BSO may be a highly effective sensitizer for chemotherapeutic treatment of BTC patients.…”
Section: Discussionmentioning
confidence: 77%
“…Although emodin provides a therapeutically feasible approach to overcome chemoresistance in gallbladder cancer cells, little clinical trial data regarding emodin is available, and the development of an emodin-based drug remains in the experimental stages. Oral ingestion of large amounts of emodin may lead to stomach cramping, gas production, bloating and diarrhea (15)(16)(17). Therefore, it is considered that emodin tends to exacerbate the gastrointestinal side effects and contribute to patient intolerance of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%